The Mediating Effect Of Green Culture Between Ghrp And Green Sustainable Performance In Jordanian Manufacturing Companies Towards Sustainable Development Goals - Ashraf Ibrahim Abdallah Qahman; Murad Ali Ahmad Al-Zaqeba; Mujahid Hamood Hilal Al-Zakwani; Haneen A. Al-khawaja; Ahmad Nader Aloqaily; Mohannad Ahmad AL Momani (Brazilian Journals, 2025)
Indexed Publication (Tier 2)